Internet of Things Sebagai Alat Penentuan Lokasi Budidaya Rumput Laut Gracilaria Sp - Moh Thoriq Afif; Aulia Desy Nur Utomo; Anggi Zafia (Universitas Budi Darma, 2023)
Seaweed or commonly called seaweed is one of the abundant underwater biological resources in Indonesia, with around 8.6% of the total marine biota. Seaweed has various benefits such as for food ingredients, cosmetic ingredients and others. However, in seaweed cultivation, failure often occurs due to various factors, one of which is the presence of diseases or pests that attack seaweed. Gracilaria sp seaweed in Gerongan ponds in Pasuruan, East Java often experiences different responses when planted in different ponds. Existing environmental factors come from ponds where seaweed is planted to cause damage. This tool is made using a microcontroller to prevent crop failure and damage to seaweed in the Gerongan pond, Pasururan, East Java, namely the design of a tool for determining the location of Gracilaria Sp seaweed cultivation based on IOT. This tool uses the NodeMCU ESP8266 with the help of sensors, namely a distance sensor for water depth, a temperature sensor, a strong current sensor, and a pH sensor. The results of this study show that seaweed farmers can monitor seaweed by stabilizing the pond environment with data that has been obtained from sensor results that they can see on the Android application. This tool makes it easier for farmers to cultivate seaweed and helps improve the quality of the Grasilaria sp. seaweed harvest.